Biomechanics, Neurorehabilitation, Mechanical Engineering, Manufacturing Systems, Robotics and Aerospace : selected, peer reviewed papers from the 3th [sic] International Conference on Biomechanics, Neurorehabilitation, Mechanical Engineering, Manufacturing Systems, Robotics and Aerospace, October 26-28, 2012, Bucharest, Romania - Olaru, Adrian (Applied mechanics and materials ;, 2013)
The main objective of the special collection of 53 peer-reviewed papers was to gather some of the current knowledge from leading researchers, engineers and scientists in the field of: Biomechanics, Biomechatronics, Neurorehabilitation, Mechanical Engineering, Manufacturing Systems, Robotics, Aerospace.